2017
DOI: 10.4103/2008-322x.200171
|View full text |Cite
|
Sign up to set email alerts
|

Tolosa–Hunt syndrome demonstrated by constructive interference steady state magnetic resonance imaging

Abstract: Purpose:To highlight the role of constructive interference steady state (CISS) magnetic resonance imaging (MRI) in the diagnosis of Tolosa-Hunt Syndrome (THS).Case Report:We describe a case of THS in a 55-year-old woman presenting with left painful opthalmoplegia that was diagnosed by CISS MRI. Patient responded to steroid treatment and the lesion resolved.Conclusion:Imaging with MRI can help in making the diagnosis of THS by demonstrating an enhancing soft tissue lesion in the cavernous sinus and orbital apex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“… 15 17 Advanced MRI protocols such as constructive interference steady state, selective partial inversion recovery, and three-dimensional fast-imaging employing steady-state acquisition may help in demonstrating the causative lesion. 19 20 21 …”
Section: R Esultsmentioning
confidence: 99%
“… 15 17 Advanced MRI protocols such as constructive interference steady state, selective partial inversion recovery, and three-dimensional fast-imaging employing steady-state acquisition may help in demonstrating the causative lesion. 19 20 21 …”
Section: R Esultsmentioning
confidence: 99%
“…Specific clinical diagnostic criteria are delineated; however, literature on the radiological aspect of the diagnosis remains ambiguous [ 2 , 3 , 6 , 9 , 10 ]. This may be due to the rarity of the disease as well as the difficulty in creating detailed images of the cavernous sinus [ 2 , 3 , 9 , 10 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, MRI is the imaging modality of choice for evaluating THS, and to exclude other lesions that can involve the cavernous sinus such as lymphoma [ 1 , 4 , 7 ]. Suggestive findings of THS in MRI include enlargement and dural margin convexity, with or without T1-isointense with gray matter abnormal tissue, and isointense to hypointense on T2 sequences [ 2 , 3 , 6 , 9 , 10 , 12 ]. A limitation, however, is that MRI detects any abnormal tissue, not only granulomatous inflammation [ 2 , 3 , 6 , 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…A combination of diminished tendon reflex and extra-ocular movement disturbance advocate Miller Fisher Syndrome which mimics THS [53]. Persistent ipsilateral somatosensory loss/forehead paresthesia and decreased pinprick sensation owing to the subdivision of trigeminal nerve (ophthalmic) lesion may also be detected on examination [25] [54] [55].…”
Section: Physical Examintion/signsmentioning
confidence: 99%
“…MRI findings of THS may reveal thickening changes of the CS due to the soft tissue abnormality with or without entanglement of the internal carotid(IC) artery, SOF, OA, or optic CN, the granulomatous lesion appears as T1 isointensity sequence and iso hypointensity apperance in T2 sequences with diffusion abnormality and shows significant contrast involvement following contrast injection of the medium intravenously, Figure 1 [ [64]. Recent researches have revealed that restricted diffusion can delineate the extent of THS as precisely as the current cornerstone modality of choice (the Gadolinium-enhanced MRI) in portraying the degree of the lesion and guide treatment response by virtue of intrusion by inflammatory cells makes the inflammatory regions more evident on DWI, hence further studies of these lesions on DWI can pave a way into significant reduction total scan duration, on the side, Constructive interference in steady-state (CISS) MRI has recently been proved to have high sensitivity as well for diagnosing and follow up THS [55] [65].…”
Section: Imaging In Thsmentioning
confidence: 99%